2016
DOI: 10.1128/aac.02967-15
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Daptomycin Exposure and Efficacy and Safety Endpoints To Support Risk-versus-Benefit Considerations

Abstract: bThe choice of an antimicrobial agent must balance optimization of efficacy endpoints with the minimization of safety events. The risk versus benefit of daptomycin for patients with Staphylococcus aureus bacteremia with or without infective endocarditis receiving daptomycin at 6, 8, and 10 mg/kg of body weight/day was assessed. The relationships between the area under the concentration-time curve over 24 h (AUC)/MIC ratio and both clinical response and time to decreased susceptibility were evaluated using data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 23 publications
2
22
0
Order By: Relevance
“…In adults, daptomycin has the potential to cause CPK elevations, in particular at the higher doses used to treat bacteremia. 25 In our study, increased CPK was not more frequent in daptomycin-than in SOC-treated children, suggesting there is no need TESAE, treatment-emergent serious AE. a TEAE that occurred from the time of the fi rst dose of the study drug through the last study evaluation or preexisting AEs that were aggravated in severity or frequency during the dosing period.…”
Section: Discussionsupporting
confidence: 45%
“…In adults, daptomycin has the potential to cause CPK elevations, in particular at the higher doses used to treat bacteremia. 25 In our study, increased CPK was not more frequent in daptomycin-than in SOC-treated children, suggesting there is no need TESAE, treatment-emergent serious AE. a TEAE that occurred from the time of the fi rst dose of the study drug through the last study evaluation or preexisting AEs that were aggravated in severity or frequency during the dosing period.…”
Section: Discussionsupporting
confidence: 45%
“…Indeed, this phenomenon has also been observed using data from daptomycin-treated patients with Staphylococcus aureus bacteremia with or without infective endocarditis. At 30 days after the start of therapy, the relationship between the probability of decreased susceptibility and AUC/MIC ratio resembled an inverted-U shape (19). The strength of the in vitro hollow-fiber infection model is that drug exposures beyond those that can be attained clinically can be examined.…”
Section: Discussionmentioning
confidence: 99%
“…38 Using these data, Monte Carlo simulations suggested improved clinical success (clinical cure or partial improvement in clinical signs and symptoms not requiring further treatment) with increased daptomycin exposure among certain patient populations stratified by outcome probability of response. 38 In our study, we observed survival benefits with increased daptomycin exposure, which builds on the results of the simulation study 38 because our CART analysis identified clinical benefit with higher doses than the label daptomycin dose regimens among patients with worse survival probabilities. Two studies have suggested that a fixed daptomycin dose may be an alternative to a milligram/kilogram dose.…”
Section: Discussionmentioning
confidence: 99%
“…Before the present study, the most relevant work in determining the impact of higher daptomycin dose on clinical outcomes in patients with MRSA BSI was from simulation modeling performed using data from a randomized noninferiority study comparing daptomycin with the standard of care for right‐sided infective endocarditis . In the multivariable analysis of the simulation study, 24‐hour area under the concentration‐time curve to minimum inhibitory concentration (MIC) ratio, Cl cr clearance, albumin level, and disease category (left‐sided endocarditis, right‐sided endocarditis or complicated bacteremia, or uncomplicated bacteremia) were found to be predictors of clinical response . Using these data, Monte Carlo simulations suggested improved clinical success (clinical cure or partial improvement in clinical signs and symptoms not requiring further treatment) with increased daptomycin exposure among certain patient populations stratified by outcome probability of response .…”
Section: Discussionmentioning
confidence: 99%